Integration of paleolimnological and contemporary hydroecological analyses to decipher effects of multiple stressors on water-rich northern landscapes - MacDonald, Lauren Ashley (University of Waterloo, 2015)
Northern freshwater ecosystems provide important habitat and resources which support abundant wildlife and waterfowl populations and the traditional lifestyle of many First Nation communities. However, concerns have been mounting regarding the effects of multiple stressors, including climate change and other human-related activities in these regions. In order to understand the consequences of stressors, information on both present and past conditions is needed. This thesis addresses knowledge gaps by using a combination of contemporary and paleolimnological methods to characterize lake and pond responses to different stressors in three northern landscapes. A paleolimnological record in combination with aerial images was used to investigate causes of lake-level changes at a lake in the Old Crow Flats (OCF). Contemporary measurements were used to identify how hydrological and limnological conditions of coastal ponds in Wapusk National Park (WNP) differ seasonally and with disturbance from Lesser Snow Geese (LSG). Paleolimnological studies were also used in this landscape to determine how hydroecological conditions have changed during the past few centuries in response to climate warming and LSG population expansion. At a lake in the Slave River Delta (SRD), paleolimnological studies of hydrology and contaminant deposition were used to establish baseline concentrations and assess if temporal changes have occurred in response to northern industrial development. Together, these studies provide a detailed record of environmental changes in response to stressors at three large northern freshwater landscapes. Recent studies using remote sensing analysis of lake-rich thermokarst landscapes have documented evidence of declining lake surface area in response to recent warming. However, images alone cannot identify whether these declines are due to increasing frequency of lake drainage events associated with accelerated thermokarst activity or to increasing evaporation in response to longer ice-free season duration. In Chapter 2, the potential of combining aerial photograph time series with paleolimnological analyses to track changes in hydrological conditions of a thermokarst lake in the OCF and to identify their causes was explored. Images showed water level in lake OCF 48 declined markedly sometime between 1972 and 2001. In a sediment core from OCF 48, complacent stratigraphic profiles of several physical, geochemical and biological parameters from ~1874-1967 indicated hydrolimnological conditions were relatively stable. From ~1967-1989, declines in organic matter content, organic carbon isotope values and pigment concentrations were interpreted to reflect an increase in supply of minerogenic sediment, and subsequent decline in aquatic productivity caused by increased thermo-erosion of shoreline soils. Lake expansion was likely caused by increased summer rainfall, as recorded by increased cellulose-inferred lake-water oxygen isotope compositions. Stratigraphic trends defining the lake expansion phase terminated at ~1989, which likely marks the year when the lake drained. Above-average precipitation during the previous year probably raised the lake-level and promoted further thermo-erosion of the shoreline soils that caused the lake to drain. These are meteorological conditions that have led to other recent lake-drainage events in the OCF. Thus, the decline in lake-level evident in the aerial photograph from 2001 is unlikely to have been caused by evaporation, but rather is a remnant of a drainage event that took place more than a decade earlier. After drainage, the lake began to refill, and most paleolimnological parameters approached levels that are similar to those during the stable phase. These findings indicated that combined use of aerial images and paleolimnological methods offers much promise for identifying the hydrological consequences of recent climatic variations on thermokarst lakes. The past ~40 years have seen a geometric increase (5-7% per year) in the Lesser Snow Goose (LSG) population (Chen caerulescens caerulescens) and marked spatial expansion of the area they inhabit within the coastal fen ecotype of WNP (Hudson Bay Lowlands, northern Canada), raising concerns and uncertainty about the environmental effects of their activities (grubbing of vegetation, soil disturbance, deposition of feces) on the abundant shallow tundra ponds. In Chapter 3, conventional limnological measurements as well as water and carbon (C) isotope tracers were used to explore similarities and differences in seasonal patterns of hydrological, limnological and biogeochemical conditions of 15 shallow coastal fen ponds that currently have minimal (if any) disturbance from the LSG population with one pond (WAP 20) that is subject to substantial LSG activity. Carbon isotope measurements reveal that C cycling at WAP 20 (LSG disturbed site) is markedly different compared to the other ponds, whereas only small differences were observed in hydrological conditions and concentrations of major nutrients and chlorophyll a of pond water. A mid-summer decrease in C isotope composition of dissolved inorganic carbon (DIC) occurred at WAP 20, likely as a consequence of high pond-water pH and intense C demand by aquatic productivity. These conditions appear to have promoted ‘chemically-enhanced CO2 invasion’, which causes strong kinetic C isotope fractionation. High C demand at WAP 20 is also suggested by mid-summer 13C-enrichment in particulate organic matter. In contrast, the ponds with little to no LSG activity exhibited expected seasonal C isotope behaviour (i.e., 13C-enrichment of DIC) under conditions of increasing productivity when C is in relatively low demand. Small differences in nutrient concentrations may be due to rapid uptake by the benthic mat at WAP 20. Data from the low disturbance ponds also provide baseline information for future studies assessing potential effects of LSG. Shallow lakes are dominant features in Subarctic and Arctic landscapes and are responsive to multiple stressors, which can lead to rapid changes in limnological regimes with consequences for aquatic resources. In Chapter 4, this theme was addressed in the coastal tundra region of WNP. Integration of limnological and paleolimnological analyses document profound responses of productivity, nutrient cycling and aquatic habitat to warming at three ponds (‘WAP 12’, ‘WAP 20’, ‘WAP 21’), and to LSG disturbance at the two ponds located in an active nesting area (WAP 20, WAP 21). Based on multi-parameter analysis of 210Pb-dated sediment records from all three ponds, a regime shift occurred between 1875 and 1900 CE marked by a transition from low productivity, turbid, and nutrient-poor conditions of the Little Ice Age to conditions of higher productivity, lower nitrogen availability, and the development of benthic biofilm habitat as a result of climate warming. Beginning in the mid-1970s, sediment records from WAP 20 and WAP 21 reveal a second regime shift characterized by accelerated productivity and increased nitrogen availability. Coupled with three years of limnological data, results suggest that increased productivity at WAP 20 and WAP 21 led to atmospheric CO2 invasion to meet algal photosynthetic demand. This limnological regime shift is attributed to an increase in the supply of catchment-derived nutrients from the arrival of LSG and their subsequent disturbance to the landscape. Collectively, findings discriminate the consequences of warming and LSG disturbance on tundra ponds from which we identify a suite of sensitive limnological and paleolimnological measures that can be utilized to inform aquatic ecosystem monitoring. Growth of natural resource development in northern Canada has raised concerns that activities pollute downstream aquatic ecosystems, but insufficient knowledge of pre-industrial baseline conditions continues to undermine ability of monitoring programs to distinguish industrial-derived contaminants from those supplied by natural processes. In Chapter 5, a novel paleolimnological approach was used to define pre-development baseline concentrations of 13 priority pollutant metals and vanadium and assess temporal changes, pathways and sources of these metals at a flood-prone lake in the SRD (NWT, Canada) located ~500 km north of Alberta’s oil sands development and ~140 km south of a former gold mine at Yellowknife, NWT. Results identify that metal concentrations, normalized to lithium concentration, were not elevated in sediments deposited during intervals of high flood frequency or low flood frequency since onset of oil sands development (post-1967) relative to the 1920-1967 baseline established at the study lake. When compared to a baseline for the lower Athabasca River, several metal-Li relations (Cd, Cr, Ni, Zn, V) in post-1967 sediments delivered by floodwaters appear to plot along a different trajectory, suggesting that the Peace and Slave River watersheds are important natural sources of metal deposition at the SRD. However, analysis revealed unusually high concentrations of As deposited during the 1950s, an interval of very low flood frequency, which corresponded with emission history of the Giant Mine gold smelter indicating a legacy of far-field atmospheric pollution. Our study demonstrates the potential for paleolimnological characterization of baseline conditions and detection of pollution in floodplain ecosystems, but that knowledge of paleohydrological conditions is important for accurate interpretations. Through the integration of paleolimnological and contemporary hydroecological analyses this thesis was able to decipher the effects of multiple stressors on water-rich northern landscapes.
Keywords: Paleolimnology; Carbon; Wapusk National Park; Old Crow Flats; Slave River Delta; Thermokarst lakes; Lesser Snow Goose; Metals; Giant Mine; Biology